CONVERGENCE OF STYLISTIC DEVICES IN MYSTIC POETRY (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
A literary work is a product of artistic language, and therefore, the language of a literary work depends on the author's skill and the possibilities of the language. Writers and poets choose words and expressions to create imagery and scenes, determining their literal and figurative meanings, identifying synonyms and antonyms, and using syntactic structures of the national language. That is why literature is called “the art of depicting life through words.” Research indicates that the language of a literary work is the only means of realizing its content.